SINTESIS DE LA COCARBOXILASA POR DISTINTOS TEJIDOS DE PROCEDENCIA ANIMAL - ROCA, JUAN; LLAMAS, ROBERTO (Hospital General, Laboratorio del Tifo, CD MEXICO, DF, MEX, 1941)
The author believes that the construction of a Pan American highway will create many problems of medico-entomologic nature Such diseases as leishmaniasis, orchocerciasis, oroya fever, yellow fever, and malaria, which are transmissible by insects and whic
ANS INST BIOL
Keywords: SINTESIS, COCARBOXILASA, DISTINTOS TEJIDOS, PROCEDENCIA ANIMAL; CIENCIAS DE LA VIDA; BIOFISICA; FISICA MEDICA